Clara - Grundtvig, N. F. S. (Grundtvig-Studier, 1985)
Clara By N. F. S. Grundtvig Grundtvig published this poem in his periodical The Dane on November 8th 1848. It is reprinted here as it appeared in the original edition. Clara is a description of his meeting with a woman in a foreign country, whom he met once only but who according to another poem, The Little Ladies, inspired much of his later poetry. Her importance for Grundtvig has been described in detail by Kaj Thaning in his thesis, Man First - (1963, see esp. pp. 220-31) An earlier treatment is by J. P. Bang in Grundtvig and England (1932 pp. 62-83).